Characterizations Of Bio-Asphalt Using Palm Bio-Oil From Empty Fruit Bunches And Beta Carotene - Mok, Tai Han (Universiti Sains Malaysia, 2021)
The depletion of petroleum resources around the world has sparked interest among researchers in looking for potential alternative binders. Bio-asphalt is eventually categorized as a high potential binder to replace petroleum-based asphalt due to its similar rheological properties, renewable resources, and environmental friendliness. In this study, the palm bio-oil derived from waste empty fruit bunches (WBO) and beta carotene bio-oil (CBO) were added into the conventional asphalt binder at 5%, 10%, and 15%. The properties of bio-asphalt made of WBO and CBO were investigated. Initially, the physical and rheological properties of bio-asphalts were assessed using penetration test, softening point test, rotational viscosity test, ductility test, specific gravity test, and mass loss after short-term aging process via rolling thin film oven (RTFO). Then, the FTIR and GC-MS tests were carried out to identify the chemical compositions and functional groups of both bio-asphalts. Furthermore, the asphalt mixtures were prepared via Marshall method to determine the optimum binder content (OBC), and the effect of bio-oil on volumetric properties and mechanical performances of asphalt mixtures was addressed. Finally, the service characteristics were assessed using static water immersion and water boiling tests. The addition of bio-oil results in a lower softening point, viscosity, and ductility, while increasing the penetration, specific gravity, and mass loss after RTFO. FTIR analysis shows the functional groups of WBO were mainly phenol, alcohols, ketones, aldehydes, and carboxylic acids. The FTIR spectra analysis of bio-asphalts was almost similar to the control asphalt. From the Marshall mix design, all asphalt mixtures meet the standard requirements of the JKR. The 10% WBO bio-asphalt mixture, on the other hand, outperforms in terms of volumetric properties and mechanical behavior. The service characteristics results show that the bio-asphalt mixtures have better bonding and coating performance as compared to the control asphalt mixture. In summary, the properties of WBO bio-asphalt are comparable to the conventional asphalt binder. Whereas the addition of WBO could produce comparable, if not superior properties to the control binder. As a result, it is recommended that WBO can be used as a partially replaced ingredient in the production of bio-asphalt, whereas CBO has a high potential for use as a rejuvenator in the improvement of the properties of highly aged asphalt mixtures.